2012
DOI: 10.1016/j.jtcvs.2012.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ascending aorta distensibility relates to adverse ventricular mechanics in patients with hypoplastic left heart syndrome: Noninvasive study using wave intensity analysis

Abstract: Using a novel, noninvasive technique based on image analysis, we have demonstrated that aortic arch reconstruction in children with hypoplastic left heart syndrome is associated with reduced aortic distensibility and unfavorable ventricular-vascular coupling compared with those with single ventricle physiology without aortic arch reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 25 publications
8
39
0
1
Order By: Relevance
“…These results indicate that SV dysfunction seems relatively unrelated to volume overload but is probably more affected by afterload conditions, as previously described [17][18][19]. Based on our results and current studies that investigated the effect of additional volume overload through aortopulmonary shunt implantation in BCPC-patients [20,21], it is unlikely that a mild or moderate amount of APC flow leads to myocardial dysfunction.…”
Section: Discussionsupporting
confidence: 86%
“…These results indicate that SV dysfunction seems relatively unrelated to volume overload but is probably more affected by afterload conditions, as previously described [17][18][19]. Based on our results and current studies that investigated the effect of additional volume overload through aortopulmonary shunt implantation in BCPC-patients [20,21], it is unlikely that a mild or moderate amount of APC flow leads to myocardial dysfunction.…”
Section: Discussionsupporting
confidence: 86%
“…Reduced aortic distensibility and deficiency in ventricular arterial coupling in single-ventricle patients may partly explain this finding. 10 One could also suspect that a low threshold for arch reintervention should be applied in patients with single ventricles. It was surprising to note that common atrioventricular morphology did not predict any adverse outcome and one could wonder whether this fact is not a consequence of a progressively more aggressive management of atrioventricular valve regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…The fate of the reconstructed aorta in HLHS has been assessed in previous studies 1, 2, 3. Cardis et al found increased stiffness and decreased distensibility in the reconstructed aortic arch by using echocardiography 3.…”
Section: Introductionmentioning
confidence: 99%
“…Cardis et al found increased stiffness and decreased distensibility in the reconstructed aortic arch by using echocardiography 3. In a cardiac magnetic resonance imaging (CMR) study of a small cohort of HLHS patients (n=10), Biglino et al reported greater aortic pulse wave velocity (PWV) and reduced distensibility of the ascending aorta 2. In addition, they found lower ascending aortic wave intensity and energy, suggesting abnormal ventricular–vascular coupling 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation